A method for manufacturing a dehumidification wheel

By mixing glass fiber and other materials in a certain proportion and forming honeycomb bodies, and then converting silicon hydrogel into silicon aerogel, the existing glass fiber paper rolling honeycomb bodies are solved, and the problem of complex and high cost is achieved. Efficient dehumidification and simplified production process.

CN119186535BActive Publication Date: 2025-02-21HANGZHOU PURUI DEHUMIDIFICATION EQUIP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411710134.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

There are many process steps for rolling honeycomb bodies with long processing cycles, which can easily lead to product defects and increase manufacturing costs.

Method used

Mix glass fiber, glass fiber cotton, diatomaceous earth, water glass, alkaline aluminum chloride, acrylic resin and water in a certain proportion to form a honeycomb body, and then soak to form a silicon hydrogel, which is converted into silicon gas after drying. Gel, simplify process steps and shorten processing cycles.

Benefits of technology

The process steps and processing cycles of manufacturing honeycomb bodies are reduced, the defective rate and manufacturing cost are reduced, and the dehumidification effect and efficiency are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186535B_ABST
    Figure CN119186535B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for making a dehumidification wheel, comprising the following steps: (1) glass fiber: glass fiber cotton: water glass solution: basic aluminum chloride solution: diatomaceous earth: acrylic resin is mixed and stirred to form a mixture; (2) the mixture is placed in an inverted honeycomb mold, compacted with a perforated plate to obtain a semi-dried honeycomb body; (3) hot air drying; (4) water glass solution impregnation; (5) repeating steps (3) and (4); (6) immersion in a sulfuric acid solution containing titanium sulfate; (7) washing with water and drying with hot air to constant weight; (8) removing organic matter contained; (9) cutting and assembling into a dehumidification wheel. The cell density of the honeycomb body made by the present invention is greater than that of the honeycomb body rolled from glass fiber paper, and can absorb moisture more effectively. The secondary water glass solution impregnation carries more dehumidification medium than the traditional method, thereby improving the dehumidification capacity per unit volume of the honeycomb.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of separation technology, and in particular relates to a method for manufacturing a dehumidification wheel. Background Art

[0002] The earliest dehumidification wheel was invented by Carl Montes of Sweden in the 1950s and was perfected in the 1960s. At that time, asbestos paper was impregnated with halogen salts such as lithium chloride and then corrugated, bonded, wound, and heat-treated (US pat.3,231,409, 3,307,617, etc.). Asbestos fiber is soft, hydrophilic, easy to be pulped and separated into fibers, and has abundant hydroxyl groups on the fiber surface. After the paper sheet is formed, hydrogen bonds can be formed between the fibers. The paper is soft and has good tensile strength, which is suitable for subsequent corrugation processing. However, asbestos fiber has potential carcinogenicity, which limits its further use. Today, the base material of the dehumidification wheel is mostly glass fiber paper (US pat.4,871,607, US pat.4,886,769, US pat.5,423,934).

[0003] Glass fiber is not easy to disperse in water and needs a dispersant to maintain the fiber suspension. It has a smooth surface and cannot be separated by pulping. Therefore, the fibers cannot be bonded together by hydrogen bonds to form paper during papermaking. Adhesives such as PVA must be sprayed on the wet paper and then dried to make paper (CN112663398).

[0004] The above-mentioned glass fiber paper is used as a substrate and impregnated with a water glass solution. After partial drying, one layer is rolled into a corrugated shape and then bonded with another layer of flat glass fiber paper also impregnated with a water glass solution with an adhesive, and then rolled on another axis to form a honeycomb core wheel. After drying, the honeycomb core wheel is soaked in an acidic solution such as sulfuric acid to react to generate a silicon hydrogel, and then washed with water to remove reaction byproducts such as sodium sulfate and excess reactants. After being completely dried with hot air, the silicon hydrogel on it is converted into a silicon aerogel with hygroscopic properties. This honeycomb core wheel must also be heat treated at 200-500°C to remove organic matter used in the aforementioned process, such as cellulose pulp, organic adhesives, etc., to ensure that the honeycomb core wheel will not have the risk of smoke or even combustion during high-temperature regeneration (US pat.6,875,299, 5,423,934, 4,911,775, 4,871,607, etc.).

[0005] The above-mentioned process of making a dehumidification honeycomb rotor with glass fiber paper as a carrier is relatively long and requires many processes such as papermaking, impregnation, drying, corrugating, bonding, winding, acid treatment, washing, re-drying, and high-temperature heat treatment. Each process may cause defects to the product, thereby affecting the final quality and manufacturing cost of the rotor. Summary of the invention

[0006] In order to overcome the technical problem that the glass fiber paper rolled honeycomb body in the prior art has many process steps, each process may bring defects to the product, and the processing cycle is long, which also causes its high manufacturing cost. One purpose of the present invention is to provide a method for making a dehumidification wheel, by mixing glass fiber, glass fiber wool, diatomaceous earth, water glass, basic aluminum chloride, acrylic resin and water in a certain proportion and forming a honeycomb body in an inverted honeycomb mold, and generating a silicon hydrogel for dehumidification by immersion and converting it into a silicon aerogel after drying, thereby reducing the process steps and processing cycle of manufacturing the honeycomb body, thereby also reducing the defective rate and manufacturing cost.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: a method for manufacturing a dehumidification wheel, comprising the following steps:

[0008] (1) Mix glass fiber: glass fiber wool: water glass solution: basic aluminum chloride solution: diatomaceous earth: acrylic resin in the proportion of 0.5 parts: 0.5 parts: 10 parts: 0.5 parts: 0.5 parts: 0.1 parts by mass and stir to form a mixture;

[0009] (2) placing the mixture in an inverted honeycomb mold, placing the inverted honeycomb mold on a high-frequency vibration table, vibrating for 20 minutes, and then adding a perforated plate for compaction to allow excess water to flow out. When the mixture is squeezed dry, the inverted honeycomb mold is removed to obtain a semi-dried honeycomb body;

[0010] ⑶ Dry the semi-dried honeycomb body with hot air at 20-80° C. for 12-20 hours to obtain a dried honeycomb body;

[0011] (4) Immerse the dried honeycomb body in a water glass solution for 30 minutes at a solution temperature of 40-45° C., so that a layer of water glass is attached to the inner pore surface of the dried honeycomb body;

[0012] (5) Dry the impregnated honeycomb body completely again;

[0013] (6) Soaking the completely dried honeycomb obtained in step (5) in a sulfuric acid solution containing titanium sulfate at a pH of 1.5-3.5 for 30-90 minutes;

[0014] ⑺ Rinse the honeycomb obtained in step ⑹ with water until the washing liquid is neutral, and dry it with hot air at 120° C. to constant weight;

[0015] ⑻ heat treating the honeycomb obtained in step ⑺ for 60 minutes at 400-550° C. and an oxygen content of less than 10% to remove the organic matter contained therein;

[0016] ⑼ Cut the heat-treated honeycomb body as required and assemble it into a dehumidification wheel.

[0017] In this ratio, the glass fiber acts as a skeleton in the entire honeycomb, similar to the steel bars in concrete; the glass fiber wool can build more intersections with the glass fiber and form gaps to fix the water glass and then form silica gel in the subsequent acidification reaction; basic aluminum chloride is a strong precipitant, which can quickly deposit the water glass onto the glass fiber; the addition of diatomaceous earth can ensure a close fit with the mold, and can form smooth pores after demoulding, reducing the wind resistance of the treated air during dehumidification, and it itself is also hygroscopic; acrylic resin acts as an adhesive, which can ensure the strength of the honeycomb after curing.

[0018] Furthermore, the number of honeycomb channels on the cross section of the honeycomb body perpendicular to the honeycomb channels is 10-50 / cm 2 ; The ratio of the pore diameter to the wall thickness of the honeycomb channel is 5.0-15.0.

[0019] The thickness of conventional glass fiber paper is about 0.2 mm, the height of rolled corrugation is generally 2 mm, the width of corrugation is 3.3 mm, and there are about 15-20 channels per square centimeter. The honeycomb core of the present invention is different from the conventional honeycomb core rolled from glass fiber paper, and the number of channels can reach up to 50 per square centimeter. The greater the density of honeycomb channels, the greater the specific surface area, thereby increasing the contact area between the adsorbent and water vapor in the air.

[0020] Specifically, the solid content of the water glass solution described in step (1) and step (4) is 37.6%, and the molar ratio of SiO2 / Na2O is 3.22.

[0021] Specifically, the concentration of the basic aluminum chloride solution is 10%.

[0022] Specifically, the solid content of the acrylic resin is 40%.

[0023] Furthermore, the frame of the anti-honeycomb mold is made of a porous metal plate lined with a metal filter.

[0024] Specifically, the content of titanium sulfate in the sulfuric acid solution in step (6) is 3%.

[0025] Adding titanium sulfate to the acid solution will eventually form titanium-containing aerogel, which can improve the thermal stability of silica gel and increase its moisture absorption capacity.

[0026] Specifically, the temperature of the sulfuric acid solution in step (6) is 40-45°C; during the treatment process, the sulfuric acid solution is continuously replenished to maintain the pH between 1.5-3.5.

[0027] Furthermore, the sulfuric acid solution in step (6) circulates in the honeycomb body through a diaphragm pump.

[0028] Furthermore, the end surface of the dehumidification wheel in step (9) is sprayed with phenolic resin, epoxy resin or Teflon resin to improve its wear resistance.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The cell density of the honeycomb body produced by the present invention is greater than that of the honeycomb body rolled from glass fiber paper, which means that a larger specific surface area can be achieved, thereby increasing the contact area between the adsorbent and water vapor in the air and enhancing the dehumidification effect; at the same time, during the regeneration process, when high-temperature air passes through the rotor, the adsorbed moisture can be desorbed more effectively, thereby restoring the moisture absorption capacity of the rotor.

[0031] 2. The present invention can also be impregnated with water glass solution twice, so that the honeycomb can carry more dehumidification medium than the traditional method, thereby improving the dehumidification capacity of the honeycomb per unit volume.

[0032] 3. The manufacturing process of the present invention is simple, reduces the process flow and links, shortens the manufacturing cycle and also reduces the defective rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the process flow of the present invention;

[0034] In the figure: 1. anti-honeycomb mold; 11. porous metal plate; 12. filter screen; 2. mixture. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.

[0036] In the description of the present invention, it should be noted that directional words, such as the terms "center", "lateral", "longitudinal", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", etc., indicating directions and positional relationships are based on the directions or positional relationships shown in the accompanying drawings, which are only for the convenience of narrating the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and cannot be understood as limiting the specific scope of protection of the present invention.

[0037] In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features. Therefore, the definition of "first" and "second" features can explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "several" is two or more, unless otherwise clearly and specifically defined.

[0038] In the present invention, unless otherwise specified and limited, the terms "setting", "installation" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can also be a mechanical connection; it can be directly connected, or it can be connected through an intermediate medium, or the two elements can be internally connected. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0039] See also Figure 1 A method for manufacturing a dehumidification wheel comprises the following steps:

[0040] (1) Mix glass fiber: glass fiber wool: water glass solution: basic aluminum chloride solution: diatomaceous earth: acrylic resin in the proportion of 0.5 parts: 0.5 parts: 10 parts: 0.5 parts: 0.5 parts: 0.1 parts by mass and stir to form a mixture;

[0041] (2) placing the mixture in an inverted honeycomb mold, placing the inverted honeycomb mold on a high-frequency vibration table, vibrating for 20 minutes, and then adding a perforated plate for compaction to allow excess water to flow out. When the mixture is squeezed dry, the inverted honeycomb mold is removed to obtain a semi-dried honeycomb body;

[0042] ⑶ Dry the semi-dried honeycomb body with hot air at 20-80° C. for 12-20 hours to obtain a dried honeycomb body;

[0043] (4) Immerse the dried honeycomb body in a water glass solution for 30 minutes at a solution temperature of 40-45° C., so that a layer of water glass is attached to the inner pore surface of the dried honeycomb body;

[0044] (5) Dry the impregnated honeycomb body completely again;

[0045] (6) Soak the completely dried honeycomb body obtained in step (5) in a sulfuric acid solution containing titanium sulfate at a pH of 1.5-3.5 (most preferably pH 2.0) for 30-90 minutes (most preferably 60 minutes).

[0046] ⑺ Rinse the honeycomb obtained in step ⑹ with water until the washing liquid is neutral, and dry it with hot air at 120° C. to constant weight;

[0047] ⑻ heat treating the honeycomb obtained in step ⑺ for 60 minutes at 400-550° C. and an oxygen content of less than 10% to remove the organic matter contained therein;

[0048] ⑼ Cut the heat-treated honeycomb body as required and assemble it into a dehumidification wheel.

[0049] The number of honeycomb channels on the cross section of the honeycomb body perpendicular to the honeycomb channels is 10-50 / cm 2 ; preferably 10-25 / cm 2 The honeycomb holes are in the shape of triangle, hexagon, square, circle or other special shapes, preferably square. The honeycomb holes are evenly distributed and connected from front to back, and the ratio of the hole diameter to the wall thickness is 5.0-15.0, and the most preferred is 8.0-12.0.

[0050] Wherein, the solid content of the water glass solution described in step (1) and step (4) is 37.6%, and the molar ratio of SiO2 / Na2O is 3.22.

[0051] Wherein, the concentration of the basic aluminum chloride solution is 10%; and the solid content of the acrylic resin is 40%.

[0052] Wherein, the frame of the anti-honeycomb mold is made of a porous metal plate lined with a metal filter.

[0053] Among them, the content of titanium sulfate in the sulfuric acid solution in step (6) is 3%, and sulfuric acid as an acidic solvent can also be sulfuric acid, hydrochloric acid, phosphoric acid, or aluminum sulfate solution.

[0054] Wherein, the temperature of the sulfuric acid solution in step (6) is 40-45°C; during the treatment process, the sulfuric acid solution is continuously replenished to maintain the pH between 1.5-3.5.

[0055] Wherein, the sulfuric acid solution in step (6) circulates in the honeycomb body through a diaphragm pump.

[0056] Wherein, the end surface of the dehumidification wheel in step (9) is sprayed with phenolic resin, epoxy resin or Teflon resin to improve its wear resistance.

[0057] The wheel manufactured by the present invention is made of a slurry composed of glass fiber, glass fiber wool, water glass, basic aluminum chloride, acrylic resin, diatomaceous earth, etc., replacing the original method of glass fiber paper impregnated with water glass and then rolled into corrugated paper. Glass fiber, glass fiber wool, diatomaceous earth, water glass, basic aluminum chloride, acrylic resin and water are mixed evenly in a certain proportion, and the mixture is pressed into a honeycomb mold, and excess water is removed by vibration and compaction, and then dried and aged at 20-80°C for 12-20 hours, and the mold is removed to obtain a honeycomb body. The honeycomb body is soaked in an acidic solution such as sulfuric acid, hydrochloric acid, phosphoric acid, aluminum sulfate, etc., so that the water glass therein reacts with the acid to generate silicon hydrogel, and the byproducts of the reaction such as sodium salt and excess reactants are removed by washing with water. The silicon hydrogel is converted into silicon aerogel by hot air drying to obtain a honeycomb body with a dehumidification function, which can be made into a dehumidification wheel after cutting and processing.

[0058] Example 1

[0059] (1) Mix glass fiber: glass fiber wool: water glass solution (solid content 37.6%, SiO2 / Na2O molar ratio of 3.22): basic aluminum chloride solution (10% aqueous solution): diatomaceous earth: acrylic resin (solid content 40%) in the proportion of 0.5 parts: 0.5 parts: 10 parts: 0.5 parts: 0.5 parts: 0.1 parts by mass and stir evenly, and pour the mixture into an inverted honeycomb mold;

[0060] ⑵ The anti-honeycomb mold is placed on a high-frequency vibration table, vibrating ≥400 times per minute. After vibrating for 20 minutes, a perforated plate is added for compaction to allow excess water to flow out from the side net; the mold is removed, and the honeycomb body is sent to a hot air drying oven and dried with 80°C hot air for 12-20 hours;

[0061] ⑶ Then immerse the honeycomb in a water glass solution (solid content 37.6%, SiO2 / Na2O molar ratio of 3.22) for 30 minutes, drain and then send it into a hot air drying oven to dry it at 80°C until constant weight.

[0062] (4) The completely dried honeycomb is impregnated with a sulfuric acid solution containing titanium sulfate at pH 1.5-3.5, wherein the titanium sulfate content is 3%, and the immersion time is 60 minutes, and the temperature of the acid solution is 40-45°C. During the acid treatment process, as the acid reacts with water glass, the pH of the solution will gradually increase, and the acid needs to be supplemented to maintain the pH between 1.5-3.5. In order to fully gel the reaction, the acid can be circulated in the honeycomb with the help of a diaphragm pump.

[0063] ⑸ Take out the honeycomb, drain it and rinse it with 50℃ hot water to remove reaction byproducts such as sodium sulfate and excess reactants until the washing liquid is neutral, and dry it with 120℃ hot air to constant weight. Finally, heat treat the dried honeycomb in a non-oxygen-rich (containing 10% oxygen) environment at 400-550℃ for 60 minutes to remove the organic matter contained.

[0064] Comparative Example 1

[0065] The difference between this reference example 1 and embodiment 1 is that the secondary immersion in water glass solution in step (3) is not performed, and the other processes are consistent.

[0066] The honeycombs obtained in the above-mentioned Example 1 and Comparative Example 1 were compared with the existing honeycomb core made of glass fiber paper to evaluate their moisture absorption performance. Three honeycombs of similar volume were taken and heated in a hot air oven at 120°C to fully regenerate the adsorbent therein and then weighed. The samples were placed in an air flow at 20°C and 50%RH for 3 hours, and then weighed to calculate the moisture absorption weight gain and moisture absorption rate of the samples. The results are shown in the following table: From the data comparison analysis, we can conclude that:

[0067] 1. The moisture absorption capacity and moisture absorption rate of the honeycomb core prepared by the manufacturing method of the present invention are significantly higher than those of the conventional honeycomb body rolled from glass fiber paper, thereby being able to achieve a higher dehumidification effect and dehumidification efficiency.

[0068] 2. Due to the secondary impregnation, the honeycomb can carry more silica gel than traditional components, thereby improving the dehumidification capacity per unit volume of the honeycomb.

[0069] The above description is only a specific embodiment of the present invention, but the technical features of the present invention are not limited thereto. Any changes or modifications made by any technician in the field of the present invention are included in the patent scope of the present invention.

Claims

1. A method for manufacturing a dehumidification wheel, characterized in that: The steps include: (1) Mix glass fiber: glass fiber wool: water glass solution: basic aluminum chloride solution: diatomaceous earth: acrylic resin in the proportion of 0.5 parts: 0.5 parts: 10 parts: 0.5 parts: 0.5 parts: 0.1 parts by mass and stir to form a mixture; (2) placing the mixture in an inverted honeycomb mold, placing the inverted honeycomb mold on a high-frequency vibration table, vibrating for 20 minutes, and then adding a perforated plate for compaction to allow excess water to flow out. When the mixture is squeezed dry, the inverted honeycomb mold is removed to obtain a semi-dried honeycomb body; ⑶ Drying the semi-dried honeycomb body with hot air at 20-80° C. for 12-20 hours to obtain a dried honeycomb body; (4) Immerse the dried honeycomb body in a water glass solution for 30 minutes at a solution temperature of 40-45° C., so that a layer of water glass is attached to the inner pore surface of the dried honeycomb body; (5) Dry the impregnated honeycomb body completely again; (6) Soaking the completely dried honeycomb obtained in step (5) in a sulfuric acid solution containing titanium sulfate at a pH of 1.5-3.5 for 30-90 minutes; ⑺ Rinse the honeycomb obtained in step ⑹ with water until the washing liquid is neutral, and dry it with hot air at 120° C. to constant weight; ⑻The honeycomb body obtained in step ⑺ is heat treated for 60 minutes at 400-550° C. and an oxygen content of less than 10% to remove the organic matter contained therein; ⑼ Cut the heat-treated honeycomb body as required and assemble it into a dehumidification wheel; The number of honeycomb channels on the cross section of the honeycomb body perpendicular to the honeycomb channels is 10-50 / cm 2 ; The ratio of the pore diameter to the wall thickness of the honeycomb channel is 5.0-15.

0.

2. The method according to claim 1, characterized in that: The solid content of the water glass solution described in step (1) and step (4) is 37.6%, and the molar ratio of SiO2 / Na2O is 3.

22.

3. The method according to claim 1, wherein: The concentration of the basic aluminum chloride solution is 10%.

4. The method according to claim 1, wherein: The solid content of the acrylic resin is 40%.

5. The method according to claim 1, wherein: The frame of the anti-honeycomb mold is made of a porous metal plate lined with a metal filter.

6. The method according to claim 1, characterized in that: The content of titanium sulfate in the sulfuric acid solution in step (6) is 3%.

7. The method according to claim 1, characterized in that: The temperature of the sulfuric acid solution in step (6) is 40-45°C; during the treatment process, the sulfuric acid solution is continuously replenished to maintain the pH between 1.5-3.

5.

8. The method according to claim 1, characterized in that: The sulfuric acid solution in step (6) circulates in the honeycomb body through a diaphragm pump.

9. The method according to claim 1, characterized in that: In step (9), the end surface of the dehumidification wheel is sprayed with phenolic resin, epoxy resin or Teflon resin to improve its wear resistance.

Citation Information

Patent Citations

  • Humidity exchanger element

    US4871607A

  • Method of manufacturing dehumidifier element

    US4911775A

  • Method for producing a laminate

    US5423934A

  • Adsorption sheet and method for producing the same

    JP2021112717A

  • Method for making a humidity exchanger medium

    US5435958A